Fast Sintering of Thermoelectric Silicide Powders Using Open Die Pressing Technique. (2015) - Fanciulli, C.; Battiston, S.; Boldrini, S.; Villa, E.; Famengo, A.; Fiameni, S.; Fabrizio, M.; Passaretti, F.
Abstract: The modern study of thermoelectric materials offers two important targets: from one side the research is oriented to the development of materials with increased adimensional figure of merit, ZT, providing an improvement in energy conversion efficiency in order to make thermoelectric technology more appealing for larger scale operations. On the other hand, a hard challenge is represented by the research of novel materials based on cheaper, more reliable and less hazardous elements. This second objective is at the base of different attempts of overcoming the modern consolidated thermoelectric technology with its limits often related to the materials involved. Thermoelectric silicides, based on silicon and common metals, are interesting representatives of this second approach: the good performances in a range of temperatures able to open new fields of application for thermoelectricity, associated to the characteristics of the basic elements involved, make this class of materials a good candidate for the realization of alternative thermoelectric modules. This work presents the effects of Open Die Pressing (ODP) technique on magnesium silicide. ODP is a mechanical process, already applied to chalcogenides and Zn4 Sb3 powders, able to provide a fast sintering of the material. The low temperatures used for sintering and the short time required represent favorable technological aspects to produce thermoelectric bulks with optimal properties. Another important feature of this technique is the capability of producing textured samples, a key characteristic in some cases to optimize material performances. Magnesium silicide powders have been ODP processed obtaining dense samples. Structural analyses displayed the presence of a single phase material with no oxidation, some time observed in spark plasma sintered samples. Sintering parameters (time, temperature) have been changed looking for a reduction of grain growth during the process and for the maximization of sample density. Thermoelectric properties have been measured in the temperature range from room temperature up to 600 °C in order to evaluate effects of the processing on the starting material.